If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -18 = 2y * 7 Reorder the terms: -18 + 5y = 2y * 7 Reorder the terms for easier multiplication: -18 + 5y = 2 * 7y Multiply 2 * 7 -18 + 5y = 14y Solving -18 + 5y = 14y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14y' to each side of the equation. -18 + 5y + -14y = 14y + -14y Combine like terms: 5y + -14y = -9y -18 + -9y = 14y + -14y Combine like terms: 14y + -14y = 0 -18 + -9y = 0 Add '18' to each side of the equation. -18 + 18 + -9y = 0 + 18 Combine like terms: -18 + 18 = 0 0 + -9y = 0 + 18 -9y = 0 + 18 Combine like terms: 0 + 18 = 18 -9y = 18 Divide each side by '-9'. y = -2 Simplifying y = -2
| (2-9xy^2)x*dx+(4y^2-6x^3)y*dy=0 | | 3x+1=5+x | | y^2-5y+49=y+2 | | tan(27)=13/x | | (2x+2x)=35+5x | | -9x-13=-104 | | 5x+4x+6=2x+12 | | -38+10x=6x+66 | | -(x-7)=6x+8 | | 2(14-5y)-y=-5 | | -x-9=21 | | -22-4x=-74 | | -x-59=53+6x | | y/2+21.5=26 | | 7/125+15=-17 | | 7n-(-16)=100 | | 4h+2t=58 | | x-0.9y=2.8 | | 3x-5=y+6 | | x+12=4x-3 | | 9(42)-9(4)=9(30)+9(z) | | x^3-5x^2+4x=10 | | 4-8b^2=-100 | | 30+18*x=87 | | 30+19x=87 | | ln*5x=3 | | y^18/(25x^34z^28) | | 2x-72/x^3=0 | | 1.2x+3.7=4.5x | | -28-y=-7 | | 1/8x=16 | | 1/8x+16 |